Edukasi dan Layanan Pemeriksaan Kesehatan sebagai Upaya Mewujudkan Gerakan Masyarakat Hidup Sehat - Salman, Yuliana; Perdani, Rizki; Pratiwi, Wulan (Universitas Baiturrahim, 2024)
Anemia is a health problem that can occur in all age groups, from toddlers to old age. Anemia in pregnant women can increase the risk of premature birth, maternal and child death, and infectious diseases. Iron deficiency anemia in the mother can affect the growth and development of the fetus/baby during pregnancy and afterward. The 2018 Riskesdas results stated that in Indonesia 48.9% of pregnant women experienced anemia. As many as 84.6% of anemia in pregnant women occurs in the 15-24 year age group. Hemoglobin examination and education are one of the preventive measures for disease in order to increase public awareness about the condition of their respective bodies in order to create a Healthy Living Community Movement (GERMAS). This service activity was carried out on Sunday, May 7 2023, located in the Siring area, Banjarmasin City, which was attended by 43 participants. The activity stages began with group healthy exercise, registration, blood pressure and hemoglobin checks, consultation and distribution of snacks (mung bean porridge) and multivitamins. People who take part in this activity gain additional knowledge and are motivated to routinely check their health condition at the nearest health agency. Apart from that, providing multivitamins also increases people's nutritional intake to improve their health status.